2018
DOI: 10.1002/app.47000
|View full text |Cite
|
Sign up to set email alerts
|

Vanillin‐based polymers: IV. Hydrovanilloin epoxy resins

Abstract: In this study, hydrovanilloin synthesized by electrochemical dimerization of vanillin has been used as a renewable substitute for bisphenol A for the preparation of epoxy resins. The reaction of the disodium salt of hydrovanilloin:epichlorohydrin 1:2 mol ratio at 80°C for 30 min in water gave a hydrovanilloin – diglycidyl ether phenoxy resin. This hard thermoplastic resin showed Tg of 135°C and stable up to 255°C in air. On the other hand, the disodium salt of hydrovanilloin:epichlorohydrin 1:4 mol ratio at 80… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 58 publications
0
26
0
Order By: Relevance
“…EP resin showed outstanding mechanical properties like tensile strength (80.3 MPa) and tensile modulus (2.7 GPa) than the cured DGEBA. Amarasekara and coworkers synthesized the hydrovanilloin epoxy monomer (HVEM) using the electrochemical dimerization of VN, followed by the transformation of epichlorohydrin with NaOH ( Figure 8 c) [ 106 ]. Moreover, the hydrovanilloin epoxy resin (HVER) was prepared by the curing of various aliphatic amines such as 1,2-diaminoethane (1,2-DAE), 1,4-diaminobutane (1,4-DAB), 1,6-diamino hexane (1,6-DAH), and IPDA.…”
Section: Vn-based Resinsmentioning
confidence: 99%
“…EP resin showed outstanding mechanical properties like tensile strength (80.3 MPa) and tensile modulus (2.7 GPa) than the cured DGEBA. Amarasekara and coworkers synthesized the hydrovanilloin epoxy monomer (HVEM) using the electrochemical dimerization of VN, followed by the transformation of epichlorohydrin with NaOH ( Figure 8 c) [ 106 ]. Moreover, the hydrovanilloin epoxy resin (HVER) was prepared by the curing of various aliphatic amines such as 1,2-diaminoethane (1,2-DAE), 1,4-diaminobutane (1,4-DAB), 1,6-diamino hexane (1,6-DAH), and IPDA.…”
Section: Vn-based Resinsmentioning
confidence: 99%
“…in the synthesis of a hydrovanilloin-formaldehyde copolymer 21 or a hydrovanilloin-diglycidyl ether phenoxy resin. 22 Another electrochemical approach exploiting the same reaction type of pinacolization is the synthesis of polyvanillin by reductive polymerization of 6,6 0 -dihydroxy-5,5 0 -dimethoxy-(1,1 0biphenyl)-3,3 0 -dicarboxaldehyde, commonly called divanillin or 5,5 0 -bis-vanillin (Scheme 2). The feasibility of this synthesis was shown by Amarasekara et al in 2012 at a lead cathode in 1 M sodium hydroxide solution leading to a total vanillin-based polymer.…”
Section: Introductionmentioning
confidence: 99%
“…29 In a more recent effort we have shown that hydrovanilloin synthesized by electrochemical dimerization of vanillin can be used as a renewable substitute for bisphenol A for the preparation of epoxy resins. 30 The reaction of equivalent amounts of the disodium salt of hydrovanilloin with epichlorohydrin gave a hydrovanilloin–diglycidyl ether phenoxy resin with Tg 146°C. On the other hand, two equivalents of epichlorohydrin with hydrovanilloin gave a curable oligomer of hydrovanilloin–diglycidyl ether with 2.1 repeating units.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, this oligomer could be cured with various aliphatic diamines to give hard epoxy resins with Tg values in the range of 116–149°C. 30…”
Section: Introductionmentioning
confidence: 99%